Student progress monitoring for continuous value-added mathematics achievements / Nur Faridah Mohamed Yaziz and Noraini Noordin - Mohamed Yaziz, Nur Faridah; Noordin, Noraini (UiTM Cawangan Perlis, 2018)
Student progress monitoring helps a teacher to define a student's current performance level on skills to be learned in a year, identifies his year-end achievement goals, and establishes the progress rate at which he must work to achieve the goal. A teacher is also able to create and strategize effective teaching approaches to cater for a student's level of readiness and learning needs and fulfil appropriate stretch goals for further learning. While there are many existing assessment tools for teachers and the school system to use at monitoring a student's proficiency in Mathematics, this article has chosen to share findings related to the application of the easy and simple to use Expected Target Result (ETR) approach in one of the districts in Malaysia. Using average school grades in the Year Five examination as Take-Off Value, the approach was able to provide information on the progress of all students and all schools according to subject and type of school. Based on the benchmarks generated for each subject by this approach, teachers were able to define effective teaching methods to cater for continuous progress in students' work.